Bar Model as Intervention in Solving Word Problem Involving Percentage - Abdul Gani, Maimunah; Tengah, Khairul Amilin; Said, Hardimah (International Journal on Emerging Mathematics Education, 2019)
This experimental case-study examined the performance of convenient sampling of fourty-five Year 9 students in solving word problems involving percentage from two classes in one government secondary school in Brunei Darussalam, using Bar Model as a solving strategy. Data was gathered quantitatively through written tests in the form of six word problem items as pre-test and post-test.  The mean score of the pre-test was 0.93 indicating that the performance of the participating Year 9 students in solving word problems involving percentage was low prior to intervention. Intervention lessons produced a gain in the post-test mean to 2.87.  Although the mean of post-test marks is still lower than the passing mark of the test, paired-sample t-test provided evidence of significance, thus proving that Bar Model Method had positive effect to the performance of word problem involving percentage. Evidence also indicated an increase in the students’ overall marks  from pre-test to post-test, with almost all except two students failed the pre-test to twenty-six students achieving marks above passing mark of 3 in post-test.  Item-by-item analysis showed increase in correct responses in every item in post-test, even those with no attempts in pre-test.  These provided further evidence that there is overall improvement in students’ performance in word problems related to percentage after the use of Bar Model as intervention.